Assessment of Plasma Zinc and Total Leukocyte Count in Calves Experimentally Infected with Mannheimia haemolytica - Galarza, Esteban Martín (2020)
Mannheimia haemolytica is the main bacterial pathogen isolated in bovine respiratory disease (BRD), a common disease affecting calves before weaning. Previous research has shown that experimental infection with bovine herpesvirus 1, a respiratory virus, decreases plasma zinc (Zn) levels. However, changes in plasma Zn concentrations in calves experimentally infected with M. haemolytica have not been studied thus far. The objective of this study was to evaluate the effect of experimental infection with M. haemolytica on plasma Zn concentration in calves. Total leukocyte count and bovine respiratory disease (BRD) clinical score were also evaluated. We conducted a 6-day trial in 14 male Holstein calves randomly assigned to one of two groups, experimental (EG, n = 8) and control (CG, n = 6). Animals in EG were intrabronchially inoculated with M. haemolytica (6.5 × 106 CFU/mL) on day 0 of the trial. Plasma Zn levels were affected by time, treatment, and time by treatment interaction, being lower in EG compared with CG on days 1, 2, and 3. Differences in total leukocyte count were significant on day 1, observing a tendency on day 3. BRD clinical score differed between groups, being higher in EG throughout the trial. We conclude that experimental M. haemolytica infection reduced plasma Zn concentration in clinically ill calves, suggesting that the clinical condition of animals (healthy/ill) should be considered to better interpret plasma Zn values.